EFFECTS OF THE COMPUTER-AIDED INSTRUCTIONAL PACKAGE AND THREE DIMENSIONAL VISUALS ON THE PERFORMANCE OF SECONDARY SCHOOL STUDENTS IN BIOLOGY - Yaki, A. A.; Chukwu, Nnennaya (Sokoto Educational Review, 2013)
This study aims to investigate the effects of the Computer-Aided Instructional Package (CAIP) and three-dimensional visuals on the performance of secondary school students in Biology. The design of this study is the pretest-posttest control group design. The participants of the study consist of 68 students; 24 in the experimental group 1, 24 in the experimental group 2 and the control group has 20. The experimental group 1 received instruction via the CAIP, experimental group 2 receives instruction via three-dimensional visuals while the control group received instruction via the conventional method. The treatment lasted for four weeks. The instrument for data collection is Biology Achievement Test (BAT). The method of data analysis is the One-way Analysis of Variance (ANOVA) and t-test. The result of the study reveals that there is a statistically significant increase in the achievements of the experimental group and experimental group 2 more than the control group. There were no gender effects in the two experimental groups. It was concluded that CAIP and three dimensional visual improve secondary school students ’performance in biology. It was recommended among others that Workshop on production and utilization of instructional materials especially computer-aided instructional packages and models should be organized for secondary school teachers.